ChemInform Abstract: Oxidative Fluorination of N‐Arylsulfonamides. Issue 13 (March 2016) - Buckingham, Faye; Calderwood, Samuel; Checa, Begona; Keller, Thomas; Tredwell, Matthew; Collier, Thomas Lee; Newington, Ian M.; Bhalla, Rajiv; Glaser, Matthias; Gouverneur, Veronique
Abstract: N‐arylsulfonamides para substituted with a tert‐butyl group on the aniline are regioselectively fluorinated by ipso substitution of the tert‐butyl group.